凱利方格法在科學教育研究的應用 Application of Kelly's Repertory Grid Technique in Research on Science Education - 林裕仁 Yu-Ren Lin; 林日宗 Jih-Tsung Lin; 洪振方 Jeng-Fung Hung (National Taiwan Normal University, 2016)
本研究以文獻回顧的方法探索凱利方格法的原理與策略，再反思科學教育研究領域中可應用凱利方格法進行研究的契機與限制。凱利方格法的分析與探索主要包含下列階段：元素與構念的萃取、方格的建構與評比，以及方格的分析與解釋。這些資料分析的過程對教育研究而言具備以下優勢。首先，研究者透過凱利方格法的應用，建立有系統的資料蒐集與彙整架構，發現資料中既存的脈絡。再者，凱利方格法除了能針對單一個案所反映的方格評比進行探索與分析外，也容許跨個案的比較。在科學教育相關研究中，這些優勢適合被應用於探索學生科學學習、教師專業發展，以及評鑑科學課程與教科書等。本研究最後也說明在應用凱利方格法分析時須考量的信度與效度，以及相關的研究限制，以更明確地說明使用凱利方格法分析的策略。 This paper discusses the possible application of the repertory grid technique (RGT) in science education through a literature review. We first describe the common strategies for using RGT in psychology and education research. We then explore the reasons for using RGT and the relationship between the aforementioned strategies and the purposes of studies in the literature. Finally, we explain whether and how using RGT can assist researchers in deeply exploring science education. Three basic strategies for using RGT are summarized according to a literature review: eliciting elements and constructs, constructing the grid, and analyzing the grid. RGT enables researchers to construct and reconstruct the qualitative data on the basis of quantitative analysis, which supports exploring subjects' cognitive systems and comparing subjects. In science education, studies have applied RGT for various purposes, which we categorized into three types: exploring individual cognitive systems, developing principles for teachers' professional development, and evaluating the quality of textbooks. The limitations and validations of RGT are discussed in the final section of this paper.